Call to Action: How to Tackle Emerging Nosocomial Fungal Infections - Lionakis, Michail S. (Cell Host Microbe, 2020)
Nosocomial fungal infections require a robust scientific response to complement antifungal development and the implementation of infection control measures. This Commentary discusses how a parallel effort to address fungal pathogenesis and antifungal immunity, the mycobiota and colonization resistance, and risk factors is essential to reduce the toll of these infections.